Meaning of Land: Dynamic Certification of Customary Land Management in Nagari Sungai Kamuyang - Fatasa, Uzika Putri; Erwin, Erwin; Nurti, Yevita (Universitas Andalas, 2025)
For the Minangkabau indigenous people, property in the form of customary land is an integrated and inseparable customary component. However, agrarian conflicts often erupt, including on customary land. This is the background for the birth of the Nagari Customary Land Management Certification policy by the Ministry of Agrarian Spatial Planning / National Land (ATR/BPN) Agency to provide legal certainty to Indigenous peoples—the Nagari Sungai Kamuyang Customary Land Certificate for an area of 371,095 m2. In the implementation, Bundo Kanduang and Farmer Groups decline this policy. Through ethnographic methods, the basic arguments of each party can be revealed through their interactions with customary land, such as in management cooperation, payment of land interest, and types of plants reviewed based on Nagari Sungai Kamuyang Regulation Number 1 of 2003. These three groups interpret land as property rights, and rejection is based on arguments that tend to be resistant, such as certainty in the certificate format, certainty of the subject, and sentiments on efforts to privatize Nagari Customary Land. In contrast to the Nagari Government and Badan Pengawas Ulayat, this certification is a reality because the Nagari Customary Land only authorizes the Right to use the Nagari Sungai Kamuyang Community.